Concomitant resistance mechanisms to multiple tyrosine kinase inhibitors in ALK-positive non-small cell lung cancer. (January 2019) - Yu, Yongfeng; Ou, Qiuxiang; Wu, Xue; Bao, Hairong; Ding, Yan; Shao, Yang W.; Lu, Shun
Highlights: Concomitant ALK activating mutations are more common post multi-TKI treatments. Activated bypass signaling tends to be more prevalent following multi-TKI treatments. TP53 correlates to poor PFS in patients treated with crizotinib alone. Abstract: Objectives: ALK tyrosine kinase inhibitors (TKIs), including crizotinib and several next generation TKIs, have demonstrated beneficial clinical outcomes in ALK -positive non-small cell lung cancer (NSCLC). However, resistance mechanisms following multiple TKI treatments in ALK -positive NSCLC are not fully elucidated. Materials and methods: Mutation profiles of 422 cancer-relevant genes in 52 patients with post-TKI biopsy samples were analyzed using next-generation sequencing (NGS), and compared between patients receiving crizotinib alone (n = 35) and multi-TKIs (n = 17). Results: EML4-ALK variant 3 is the most frequent ALK variants in this cohort, followed by EML4-ALK variant 1. Half of the patients harbored ALK activating mutations upon progression on crizotinib treatment. After multi-TKIs treatment, 59% of the cases developed resistant ALK mutations, and concomitant ALK activating mutations were more commonly observed in this cohort ( P  = 0.031). Specifically, ALK G1269 A, L1196 M, and C1156Y substitutions were more common in crizotinib-alone samples, while ALK G1202R was significantly more enriched post-multi-TKIs ( P  = 0.009). Activated bypass signaling tended to be more prevalent in patients post-multi-TKIs. Furthermore, dual activation of ALK and bypass signaling was more frequently found in the multi-TKIs group (5/17, 29%) in contrast to crizotinib-alone (2/35, 6%) ( P  = 0.031). Additionally, concurrent TP53 mutation demonstrated significantly shorter progression-free survival (PFS) compared with TP53 wildtype in crizotinib-alone group (median PFS: 8 vs 13 months, Hazard Ratio = 1.494, P  = 0.019). Conclusion: Concurrent ALK activating mutations and/or upregulated bypass signaling are more enriched in patients undergoing multiple ALK TKI treatments compared to crizotinib alone. Concomitant TP53 mutation correlated to unfavorable survival when receiving a single TKI crizotinib.